Bone disease after kidney transplantation - Prajantasen, Ukrit; Kurathong, Sathit (Journal of the Nephrology Society of Thailand, 2022)
Posttransplant bone disease is a major problem among kidney transplant recipients. The spectrum of disease is consistent with renal osteodystrophy, osteoporosis, fracture and osteonecrosis. The risk of osteoporosis and fracture are higher among transplant recipients than the general population due to multiple risk factors. The major risk factor is the long-term use of corticosteroid among kidney transplant recipients. Posttransplant bone disease is classified in 4 groups, i.e., high bone turnover, low bone turnover, osteomalacia, and mixed renal osteodystrophy. Many tools are available to evaluate risks of osteoporosis and bone disease. The Fracture Risk Assessment Tool (FRAX) tool is a simple method to estimate absolute risk of fracture in 10 years. The DXA scan is the imaging method chosen to measure bone mineral density (BMD). From recent data, the FRAX and DXA scans can be useful to kidney transplant recipients. However, bone biopsy is the gold standard to distinguish bone disease type. Lifestyle modification and corticosteroid minimization both are the initial steps to decrease risk of posttransplant bone disease, especially osteoporosis. The pharmacologic approach is the mainstay of treatment. Bisphosphonates, a group of antiresorptive drugs, are widely used to treat posttransplant osteoporosis and showed beneficial effects on increased BMD. These drugs are excreted by glomerular filtration and tubular secretion. Limits are placed on patients with estimated glomerular filtration rate (GFR) < 30 ml/min/1.73 m2. The other antiresorptive agent is denosumab that can be used among patients with any eGFR. Bone biopsy may be considered before initiating antiresorptive agents.